Simulation of the Jet Fire Using Atmospheric Dispersion Modeling (ALOHA): A Case Study of Natural Gas Pipeline in Istanbul, Türkiye - AKKOYUNLU, BÜLENT OKTAY (My University, 2024)
Natural gas is known as a widely used energy source in residential, business and industrial areas. During the transportation of natural gas by pipelines, accidents occur due to various reasons, which can also lead to gas output. These accidents are events that have the potential to pose important risks in terms of life and property safety, particularly in urban areas and surrounding of pipeline routings. In this study, accident scenarios were generated based on a natural gas distribution pipeline fire that occurred in Istanbul (NW Türkiye) on 28 April 2020 and the impact areas of the jet fire were calculated using the ALOHA program. The effects of source release factors (i.e., pipe length and diameter) and atmospheric conditions (i.e., wind speed, cloud cover, air temperature and relative humidity) on the thermal radiation threat distances associated with jet fire were calculated for the current and worst scenarios. As a result, it was found that pipe length and diameter have a significant effect on threat distances. In addition to the role of the synoptic circulation mechanism on the jet fire for the selected episodic event (position of low/high pressure centers), local atmospheric conditions also have an effect on the threat distance. From the modeling analysis, significant impact of wind speed, air temperature and relative humidity values on the threat distances were found. In the worst scenario, if there were strong northeasterly winds reaching 30.9 m per hour at the time of the jet fire, the threat distances would have been 21 m (red), 28 m (orange) and 42 m (yellow). This case shows that if a natural gas jet fire occurs under the influence of strong northeasterly winds (passing over the Black Sea without encountering any topographic obstacles), poisonous gas will be transported to long distances in a short time and will negatively affect social life and economy.
Keywords: Tarımsal Bilimler; Çevre Mühendisliği; Mühendislik ve Teknoloji; Agricultural Sciences; Environmental Engineering; Engineering and Technology; Tarım ve Çevre Bilimleri (AGE); Çevre / Ekoloji; ÇEVRE BİLİMLERİ; Agriculture & Environment Sciences (AGE); ENVIRONMENT/ECOLOGY; ENVIRONMENTAL SCIENCES; Çevre Bilimi (çeşitli); Fizik Bilimleri; Environmental Science (miscellaneous); Physical Sciences; ALOHA; atmospheric conditions; jet fire; natural gas; threat distance